The reverse transcriptase–RNase H: from viruses to antiviral defense. (19th February 2015) - Moelling, Karin; Broecker, Felix
Abstract : Ubiquitous, reverse transcriptase may have contributed to the transition from the RNA to the DNA world, a transition that also involved RNase H–like activities. Both enzymes shaped various genomes and antiviral defense systems as endogenous retroviruses (ERVs) and transposable elements (TEs). A close relationship between a dozen components of retroviruses and the small interfering RNA (siRNA) antiviral‐defense machinery has been characterized. Most antiviral‐defense systems involve RNase H–like enzymes destroying invading nucleic acids, RNA, or DNA. Such enzymes include RNases H, Argonaute, Dicer, Cas9, transposases, integrases, and enzymes for immunoglobulin rearrangement and splicing. Even in mammalian cells, where protein‐based defense dominates, the siRNA machinery remains active, demonstrated by increased virus production and apoptosis after Dicer knockdown. We have noticed a surprising homology between the siRNA silencing system and the interferon response, as well as to siDNA and the CRISPR system. Further, ERVs serve in defense, in addition to having roles in gene regulation and cancer.